Subgroups of a finitary linear group - Victor Bovdi; Dashkova Olga; Mohamed A. Salim; Bódi Viktor; Бовді Віктор; Дашкова Ольга (Springer-Verlag, 2019)
Abstract. Let FLν(K) be the finitary linear group of degree ν over an associative ring K with unity. We prove that the torsion subgroups of FLν(K) are locally finite for certain classes of rings K. A description of some f.g. solvable subgroups of FLν(K) are given.
https://link.springer.com/article/10.1007/s11587-019-00438-y
Keywords: finitary linear group; integral domain; commutative Noetherian ring; véges lineáris csoport; integráltartomány; kommutatív Noetherian gyűrű